SOSIALISASI BRANDING PEMPEK KOYEK 7 ULU SEBAGAI BAGIAN DARI BUDAYA KULINER KHAS KOTA PALEMBANG - Pratiwi, Diany Putri; Febrianza, Muhammad; Ardiansyah, Ardiansyah; Sintia, Sintia; Karina, Lita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
Pempek is a typical culinary dish from Palembang city made from processed fish meat mixed with sago. The fish meat used is also varied, such as mackerel, snakehead fish, and snapper. This has created various types of pempek in Palembang city, such as pempek lenjer, pempek kapal selam, pempek kering, pempek lenggang, pempek pistel, pempek bebek, pempek kulit, and so on. The method used by the author in this paper is a descriptive method. According to Ruslan (2008:12), the descriptive method aims to describe the characteristics (traits) of individuals, situations, or certain groups. This method is relatively simple and does not require a complicated theoretical basis or submission of certain hypotheses. In this writing, the author wants to emphasize the importance of branding and packaging in a business accompanied by the use of social media. From this, it is hoped that it can facilitate the dissemination of information about Pempek Koyek and the culinary products being sold. Therefore, in this article, the author hopes that this socialization can be useful and implemented in the future, not only by Pempek Koyek, but also by residents around Kelurahan 7 Ulu